Extra‐oral drainage of submandibular abscess under local anaesthetic: review of the literature and case series. (23rd March 2016) - French, K.; Brown, E.; Collin, J.; Bell, C.
Abstract: Background: Extra‐oral drainage of odontogenic abscesses is commonly performed by oral and maxillofacial surgeons. It is a potentially hazardous and expensive procedure, but in selected cases can be carried out under local anaesthetic, avoiding some of the risks and costs associated with general anaesthesia. Aim: To evaluate the management options for odontogenic abscesses. Method: A review of the literature with respect to radiological, anaesthetic and surgical techniques that facilitate extra‐oral incision and drainage under local anaesthetic. Results: A case series demonstrates the value of imaging, the Vazirani–Akinosi mandibular nerve block, a specific forcep technique and local anaesthetic extra‐oral drainage of the submandibular space. Conclusions: Oral surgeons can utilise their specialist knowledge of head and neck anatomy, local anaesthetic technique, surgical skills and specialist equipment to deliver quick and definitive treatment for odontogenic abscesses. To our knowledge, extra‐oral incision and drainage of dental abscesses is not regularly carried out under local anaesthetic. However, if removal of the causative tooth and abscess drainage can be undertaken under local anaesthetic, the risks and costs of general anaesthesia can be avoided.